Thermal Storage for Electric Vehicle Cabin Heating in Cold Weather Conditions - Hadden, Trevor (My University, 2017)
With global warming, an inevitable threat to humanity, significant efforts in all carbon emitting industries are required. Electric vehicles are a suitable alternative to the petroleum dominated automotive industry. However, obstacles like charging infrastructure and limited range still stand in the way of their continued acceptance. This limited driving range can be further reduced in cold weather due to decreased battery efficiency and increased heating load. The heating in most electric vehicles is provided by an electrical positive temperature coefficient resistor. This architecture can lead to reductions in range of over 50 %. A thermal storage system has been devised and presented in this thesis which can partially or fully offset the thermal requirements. This is accomplished by pre-heating a thermal storage tank which then uses sensible energy to provide the heat for the cabin and battery pack. The system has been shown to reduce consumption and improve driving range in low ambient temperature conditions. This system successfully offers a potential solution to the concern of large range fluctuations due to different ambient temperatures. After producing a representative electric vehicle model in AMESim, it was compared to the Nissan Leaf with acceptable errors. The range implications for this baseline electric vehicle are then presented. A coolant based, thermal storage tank is then added to the model and simulated across a variety of temperatures and thermal storage masses. The results show that an 80 kg, 80 °C coolant tank can provide all the heating requirements for a 36 km, hour and 9 minute city drive cycle. Offering a calculated consumption reduction of up to 36 % at -30 °C as compared to the baseline electric vehicle model. Furthermore, a yearly analysis was performed based on this cycle and the results have shown that an optimal 30 kg thermal storage tank can decrease the yearly average consumption by up to 20 Wh/km or 12 %.
Keywords: Thermal Storage; Electric Vehicles; Vehicle Cabin Heating